Digital Signature Trends and Forecast (2021 – 2022) for Indonesian Government Affairs - Jonathan Gerhard T; Hasanul Fahmi (Eduvest - Journal of Universal Studies, 2025)
Since 2018, the Indonesian government has issued a policy regarding Electronic-Based Government Systems. One of the steps taken is to transform documents into electronic documents. The security aspect that can be applied to electronic documents is the digital signature. After the enactment of this policy, digital signature users and transactions have increased. Increasing dynamic electronic signature transactions needs more attention. To deal with this increase in usage, anticipating and predicting the trends in digital signature usage is crucial. Trends prediction data can be used to consider capacity planning of infrastructure resources and improving user experience. The Prophet algorithm is a forecasting tool that has the ability for robust handling of time series data with strong seasonal patterns. The prophet algorithm can analyze patterns in digital signature transactions by accommodating irregular time series. Our research uses a comprehensive set of the Indonesian government’s digital signature transactions over a period of time. This dataset contains seasonal trends, like holidays, weekends, and special events. This condition makes the dataset fluctuate. This research aims to forecast trends and seasonality of digital signature transaction volumes in the future. This research demonstrates the implementation of the Prophet algorithm to digital signature transaction data. It is hoped that the forecasting data resulting from this research can be used as a model in the digital signature sector. Then this model can be used to determine infrastructure resource allocation.